Moringa oleifera Ameliorates Histomorphological Changes Associated with Cuprizone Neurotoxicity in the Hippocampal Cornu ammonis (CA) 3 Region (Nigerian Journal of Physiological Sciences, 2021)
Summary: Cuprizone-induced neurotoxicity has severally been used to study demyelinating diseases like multiple sclerosis (MS), adversely affecting both the white and grey matters of the brain. Lesions have been observed in different regions of the brain including, corpus callosum, neocortex and the hippocampal formation. The current study explored the role of Moringa oleifera leaf extract in restoring the resultant histomorphological changes in cuprizone-induced hippocampal damage in Wistar rats. Twenty adult female Wistar rats with average weight of 163.74 ± 3.59 g were grouped into A: Control, administered with 1 ml of normal saline, B: received 0.4% cuprizone diet, C: received 1.875 mg/ml/day of Moringa extract, and D: received a combination of cuprizone and Moringa in similar doses. Administration was oral for 5 weeks. The weights of animals were assessed during treatment, and at the termination of experiment, the rats were euthanized and the brains were fixed in 4% paraformaldehyde. The tissue was processed for histological and histochemical examinations using the Haematoxylin and Eosin stain and cresyl fast violet stain to assess the general microarchitecture and neuronal cells respectively of hippocampal cornu ammonis (CA) 3 region. The body weight of cuprizone-treated rats was reduced and this was ameliorated significantly in animals that were co-administered with Moringa. Similarly, there were histological alterations in the CA3 region of the hippocampus with the presence of pyknotic pyramidal cells organized in clusters and CA3 cells with degenerative changes, but administration of Moringa led to a better organised and fairly intact histological appearance. Pharmaceutical development of Moringa oleifera into appropriate therapeutic formulations could offer some relief to patients of demyelinating conditions that have clinical features of neurological deficits.
Keywords: cuprizone; neurotoxicity; hippocampus; Moringa